A2B′B″O6 perovskites: A review - Vasala, Sami; Karppinen, Maarit (Progress in solid state chemistry, 2015)
The B-site substituted perovskite oxides A2B′B″O6 have in the recent decades gained an increasing amount of interest due to their various interesting properties and possible applications. Here we survey the literature for ca. one thousand A2B′B″O6 perovskite compounds. Crystal structures and the various crystal chemistry features such as ordering and valence mixing of the B cations characteristic to these compounds are reviewed, together with their electronic and magnetic properties. Most importantly, the thorough examination of the research so far carried out allows us to make predictions for a number of new A2B′B″O6 compounds yet to be synthesized and reveal exciting but not yet fully explored puzzles related to this family of functional oxide materials.